The Long and Short of It: Reflection on “Form” in Recent South African Fiction - Thurman, Chris (Archīum Ateneo, 2024)
This paper takes as its starting point not those aspects of “form” associated with “formalist” criticism—structure, prose style, figurative language, or other aesthetic elements—but rather the more mundane consideration of length and the related matter of genre. This is a deliberately literal (rather than literary) interpretation of “form”: what does a book look and feel like when held in the reader’s hand? What reader expectations are aroused? From the answers to these questions can be discerned certain trends in recent (post-apartheid/transitional) fiction—or, more specifically, in writing and publishing practices. In 2004, Michael Chapman identified the short story as the literary form most suited to prevailing conditions in South Africa. At the time, however, short fiction remained for the most part confined to small magazines and journals; multi-author anthologies appeared occasionally, but single-author collections were rare indeed. 2010, however, seemed to mark a resurgence of sorts: Ivan Vladislavic’s short stories (first collected in 1989 and 1996) were republished under the title Flashback Hotel, while Henrietta Rose-Innes’s Homing appeared along with Arja Salafranca’s The Thin Line and David Medalie’s The Mistress’s Dog: Stories 1996-2010. This conjunction suggests not so much an indication of renewed “writerly” interest in short fiction but regained publisher confidence in the commercial viability of the form. Michael Titlestad, in an Afterword to Medalie’s book, suggests that the (“modernist”) short story “might be particularly suited to our present” insofar as it leaves both “characters and readers on the brink of a recognition that remains ... somewhat inchoate, just out of reach ... this hesitation, this modest authorial purview, seems entirely apt.”